Pertanggungjawaban Pidana Pelaku Pembuat Website Palsu Melalui Media Sosial (Studi Putusan No: 1194/Pid.Sus/2019/PN Sby) - Toumahuw, Zirel Josilia; Adam, Sherly; Patty, Jetty Martje (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2026)
Introduction: The development of information technology has had a significant impact on various aspects of life,including cybercrimes such as the creation of fake websites through social media. So that the perpetrator can be held criminally responsible for their actions.Purposes of the Research: To analyze and discuss the judge's legal considerations in deciding the case against theperpetrator of the fake website creation through social media in Decision No. 1194/Pid.Sus/2019/PN.Sby and to analyze and discuss the criminal liability of the perpetrator of the fake website creation through social media, so that the perpetrator can be held criminally liable for their actions.Methods of the Research: The method used in this research is normative juridical, utilizing a legal problem approach, a conceptual approach, and a case approach. The legal materials used include primary legal material,secondary legal material, and tertiary legal material. The legal material collection procedure was through literature review. The legal material processing was carried out in several stages, including editing, classification, analysis, and conclusion. The legal material analysis used was qualitative analysis.Results / Findings / Novelty of the Research: The judge's legal considerations regarding the perpetrator of the fake website creation through social media in Decision No. 1194/Pid.Sus/2019/PN.Sby indicate that the judge considered legal aspects, including the public prosecutor's indictment, criminal charges, the defendant's testimony, witness testimony, evidence, and the application of articles in criminal regulations by proving all elements of Article35 of the ITE Law through valid evidence. The judge also considered non-legal aspects such as the defendant's background and the consequences of the defendant's actions and the criminal liability of the perpetrator of the fake website creation through social media. Decision No. 1194/Pid.Sus/2019/PN.Sby indicates that the defendant was legally and convincingly proven to have committed a crime as stipulated in Article 35 of the ITE Law.